Superoxide dismutase 2 ameliorates mitochondrial dysfunction in skin fibroblasts of Leber’s hereditary optic neuropathy patients - Zhou, Qingru; Yao, Shun; Yang, Mingzhu; Guo, Qingge; Li, Ya; Li, Lei; Lei, Bo (Frontiers in Neuroscience, 2022)
Background In Leber’s hereditary optic neuropathy (LHON), mtDNA mutations mediate mitochondrial dysfunction and apoptosis of retinal ganglion cells. Mitochondrial superoxide dismutase 2 (SOD2) is a crucial antioxidase against reactive oxygen species (ROS). This study aims to investigate whether SOD2 could ameliorate mtDNA mutation mediated mitochondrial dysfunction in skin fibroblasts of LHON patients and explore the underlying mechanisms. Methods The skin of normal healthy subjects and severe LHON patients harboring m.11778G > A mutation was taken to prepare immortalized skin fibroblast cell lines (control-iFB and LHON-iFB). LHON-iFB cells were transfected with SOD2 plasmid or negative control plasmid, respectively. In addition, human neuroblastoma SH-SY5Y cells and human primary retinal pigmental epithelium (hRPE) cells were stimulated by H2O2 after gene transfection. The oxygen consumption rate (OCR) was measured with a Seahorse extracellular flux analyzer. The level of ATP production, mitochondrial membrane potential, ROS and malondialdehyde (MDA) were measured separately with the corresponding assay kits. The expression level of SOD2, inflammatory cytokines and p-IκBα/IκBα was evaluated by western-blot. Assessment of apoptosis was performed by TUNEL assay. Results LHON-iFB exhibited lower OCR, ATP production, mitochondrial membrane potential but higher level of ROS and MDA than control-iFB. Western-blot revealed a significantly increased expression of IL-6 and p-IκBα/IκBα in LHON-iFB. Compared with the negative control, SOD2 overexpression increased OCR, ATP production and elevated mitochondrial membrane potential, but impaired ROS and MDA production. Besides, western-blot demonstrated exogenous SOD2 reduced the protein level of IL-6 and p-IκBα/IκBα. TUNEL assays suggested SOD2 inhibited cells apoptosis. Analogously, in SH-SY5Y and hRPE cells, SOD2 overexpression increased ATP production and mitochondrial membrane potential, but decreased ROS, MDA levels and suppressed apoptosis. Conclusion SOD2 upregulation inhibited cells apoptosis through ameliorating mitochondrial dysfunction and reducing NF-κB associated inflammatory response. This study further support exogenous SOD2 may be a promising therapy for the treatment of LHON.